Indicadores entomológicos para Aedes aegypti (Díptera: Culicidae) em suas formas imaturas e relação com transmissão do dengue - Fávaro, Eliane Aparecida (2010)
Dengue is considered the most important viral disease transmitted by the mosquito Aedes aegypti. Vector control is one alternative to reduce the number of cases and should focus on appropriate methods of entomological surveillance. Objectives: To assess the trends of entomological indicators for Aedes aegypti based on its immature forms and to evaluate its relation to dengue transmission. Material and Method: The study was carried out in São José do Rio Preto, from December 2006 to May 2009. To obtain the indicators, a research team visited buildings, counted breeding containers and collected larvae and pupae, which were placed in flasks containing 80% alcohol and sent for identification and counting. Only confirmed cases of autochthone Dengue fever registered on the Disease Notification Information System were considered. A concave net was made with a depth of 20 cm using a 15-cm round metal ring and finely woven cloth for the pupa- larva sampling method. This net was immersed at the water surface of large breeding containers and was moved around close to the wall of the container. Results: Houses, shops, factories, and building sites comprised 89.9% of the buildings inspected, 91.9% of the buildings with pupae, a productivity of 92.7% and the highest number of pupae per hectare. Undeveloped plots of land, town squares and apartments had smaller numbers of pupae per hectare. The indicators calculated per region mirrored the occurrence of Dengue fever better than those calculated per building. The entomological indicators obtained in the first and second time periods respectively were: Breteau Index: 18.9 and 13.2; positive breeding containers per 100 buildings: 6.9 and 5.3; pupae per hectare: 11.6 and 9.5; and pupae per inhabitant: 0.45 and 0.19. The calibration factor to estimate the number of immature forms in large breeding containers ranged between 1.86 and 7.03. In the second stage, for larvae it ranged from 3.59 to 26.9 and for pupae it varied between 1.57 and 4.89. Conclusions: Houses, shops, factories, and building sites are important for Ae. aegypti delevopment; apartments presented low risk. The entomological indicators calculated by region were better predictors of the risk of Dengue fever than those calculated by building independent of the type of indicator utilized. The values of the entomological indicators of the two subsequent time periods were similar, but, in general, positive buildings identified in the first period were not positive in the second. The method of screening proved to be viable when applied in the field and is adequate to estimate the number of pupae however the technique needs to be improved in order to estimate the number of larvae.